Based on ABC Optimization effective Substitution-Boxes deployed using Chaotic mapping - Kaur, Manpreet; Kaur, Sarabjeet (International Journal of Computer Sciences and Engineering, 2020)
Most block ciphers contain primitive substitution boxes to add required nonlinearity. S-boxes maintain high confusion and resistance to linear and differential attacks. The protection of those ciphers depends on the force of the S- boxes used during the replacement stage. It is difficult to create encrypted, strong S-boxes which fulfill various characteristics like high non-linearity, good avalanche effect, bit-independent requirements, low differential uniformity and linear probability, etc. We proposed in this paper to create an S-box based on optimization of artificial colony bee and chaotic diagram. An initial S-Box is built to customize the algorithm to meet several features. The results of the simulation and comparison with recent proposals suggest that the proposed ABC optimization algorithm performs fairly easily and creates an S-box with a higher degree of security.